Improving Speaking Skills with theCooperative Learning Model for Think Pair Share Class V Students of SD Negeri 5 Ambon - Sarah. Sahetapy (International Journal of Education, Information Technology, and Others, 2021)
Speaking is the activity of issuing words or sounds in the form of expressions, ideas, information, which contain certain meanings. Learning to speak using thelearning model Think Pair Share gives students time to think and respond, encourage students to be more active in asking and expressing their opinions and creative in developing their ideas. During the learning process, students must be active and creative in expressing their opinions. Because speaking is the ability to convey messages in the form of thoughts, ideas, and feelings through spoken language to others (Mulyadi, et al 2000). The criteria that serve as guidelines are readability and suitability. Think Pair Share has an explicitly defined procedure to give students more time to think, ask questions, and express their opinions, and help each other (Eanes, 1997). At thestage Think, the teacher makes apperception, explains the learning objectives and submits questions or issues related to the lesson. In thestage Pair, the teacher organizes students into pairs and gives students the opportunity to discuss the answers they think are most correct. And at the final stage, namely Sharing , the teacher asks in pairs to share with other friends in the class what they have talked about.